Students` Perspectives on The Use of Preply Application in Reading Vocabulary Skills in Students - Sania Oktavia Nasution; Siti Ismahani (Universitas Islam Negeri Palopo, 2025)
This research examines how students view the Preply application as a tool for enhancing their English reading vocabulary skills, employing a qualitative case study approach. In total, there were 27 seventh-grade learners from a junior high school in Delitua who took part in the research. Information was collected through questionnaires administered before and after the study, as well as through semi- structured interviews. After utilizing Preply, students’ confidence in reading vocabulary saw an improvement of 0. 95 points on average. The results indicate that the features of Preply—such as its flexible accessibility, multimedia resources, and the availability of tutors—positively influenced student engagement, motivation, and self-sufficiency. Nevertheless, there were obstacles, including limited access to premium functionalities and insufficient integration with existing curricula. This research is based on the frameworks of Mobile-Assisted Language Learning (MALL) and Self-Determination Theory, providing valuable insights into incorporating digital tools into formal English education.